PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP HASIL BELAJAR BIOLOGI SISWA SMA NEGERI DI KABUPATEN SOPPENG - Bungawati, Bungawati; Taiyeb, A. Mushawwir; Hartati, Hartati (UNM Journal of Biological Education, 2018)
The success level of an education process can be seen from the achievement level of students learning results. Learning results are influenced by several factors. One of the internal factors that can influence learning results is intelligence. The intelligence covers intellectual intelligence, emotional intelligence, and spiritual intelligence. The objectives of the research are to discover (i) the influence of intellectual intelligence on biologi learning results, (ii) the influence of emotional intelligence on biologi learning results, (iii) the influence of emotional intelligence on biologi learning results and (iv) the influence simultaneously of intellectual intelligence, emotional intelligence and spiritual intelligence on biologi learning results. The research employed quantitative approach with ex-post facto. The data of the research were collected throught questionnaire and documentation method. The data were processed and analyzed descriptively to describe intellectual intelligence, emotional intelligence, spiritual intelligence, and the student learning results. Inferential statistics analysis to test the hypothesis by using multiple regression analysis (with significant level Î± = 0,05) with the help of SPSS 22,1 for windows program.the results of the research showed that (i) there was influence of intellectual intelligence on biology learning results, (ii) there was influence of emotional intelligence on biology learning results, (iii) there was influence of spiritual intelligence on biology learning results, (iv) there was influence simulaneously of intellectual intelligence, emotional intelligence, and spiritual intelligence on biology learning results.